CFD analysis of unsteady flows due to supercritical heat addition in high speed condensing steam - Malek N.A.; Jamaluddin S.A.; Yusoff M.Z.; Hasini H. (Penerbit UTM Press, 2023)
This study is mainly to investigate the unsteady flows due to supercritical heat addition in high speed condensing steam in steam turbines. To achieve this, condensation flow characteristic is investigated on 2D converging-diverging nozzle. A Computational Fluid Dynamics (CFD) code (FLUENT package) that adopted the Eulerian-Eulerian approach for modeling wet steam flow, was used. The condensing flow is governed by the compressible Navier-Stokes equations in conjunction with a wet steam multiphase model. The turbulence model selected for this work is Spalart Allmaras model which is based on the Reynolds Averaged Navier Stoke (RANS) model available in FLUENT. Results are then compared with previous researchers that use different methods including user defined code and experiment. The importance of this research study is to determine the accuracy of the software and method used and to compare the results with other researchers.The current work shows good agreement with the experimental data done by Skilling [1] and 2D calculations done by Yusoff et al. [2]. It is found from the numerical simulation results that the supercritical heat addition has caused the flow in the condensing steam to retard and gives rise to pressure oscillations. The unsteady supercritical heat addition reveals promising results indicating the capability of FLUENT to calculate this phenomenon which might cause instability in turbine channel. 2015 Penerbit UTM Press. All rights reserved.